2014
DOI: 10.1007/s10461-014-0760-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Geosocial Networking (GSN) Mobile Phone Applications to Find Men for Sex by Men Who Have Sex with Men (MSM) in Washington, DC

Abstract: Current advances have added geosocial networking (GSN) mobile phone applications as an option for men who have sex with men (MSM) to meet other men. This is the first study to assess GSN application use and sex-seeking behaviors of MSM recruited using venue-based sampling. Among the 379 MSM in this study, 63.6 % reported using GSN applications to find men in the past year. Nearly one-quarter of MSM had sex with a man met using a GSN application in the prior year; these men were more likely to be under 35 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
121
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 12 publications
12
121
0
Order By: Relevance
“…Much of the research on GSN app usage among MSM has been conducted in large urban areas [10,15,22,25,26], yet similar patterns of online sex-seeking are reported among MSM residing in rural and mid-size cities [27,28]. Smaller cities often differ from larger cities in terms of stigma [29,30] and availability of visible gay spaces [31][32][33].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Much of the research on GSN app usage among MSM has been conducted in large urban areas [10,15,22,25,26], yet similar patterns of online sex-seeking are reported among MSM residing in rural and mid-size cities [27,28]. Smaller cities often differ from larger cities in terms of stigma [29,30] and availability of visible gay spaces [31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…), to meet sex partners [6]. GSN apps provide information on geographic proximity between users making sexual partner-seeking quick and convenient [7][8][9][10]. Research among MSM who use GSN apps to find sex partners have shown mixed results regarding the relationship between GSN app use and risky sexual practices.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations